Student Competence in Reading the Al-Qur'an Based on Educational Background - Ibrahim M, Ibrahim M (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
The objective of this study is to characterize Qur'anic reading proficiency among students according to their educational background. This study was carried out in MTs As'adiyah Putra I Sengkang, Class VII. Qualitative descriptive research using a field and literature approach is the research methodology employed. Inductive, deductive, and comparative methods of data analysis are employed in conjunction with observation, interviews, and documentation techniques for data collection. According to the research findings, students in class VII generally have high motivation and a high willingness to learn the Al-Qur'an, regardless of their educational backgrounds. This indicates that the students' motivation to read the Qur'an is similar. They are all enthusiastic about learning the Koran, whether from Madrasah Ibtidaiyah or religious schools, or from elementary schools or public schools. Students' fluency in reading the Al-Qur'an based on their educational background in class VII is generally the same; all of them are fluent in just reading without paying attention to their fluency and recitation. However, in particular, the new students I tested were more fluent in madrasas than in elementary schools. Meanwhile, the student's ability to recite the Al-Qur'an is based on their educational background in class VII, namely reading the Al-Quran. Students with a background from Madrasah Ibtidaiyah are able to read the Al-Quran fluently with the correct makharijul letters, correct tajwid, waqaf wal proper ibtida', as well as the art and rhythm of good tartil in reading the Koran. Meanwhile, students with an elementary school background can read the Koran fluently but are still lacking in correct makhaharijul letters, tajwid (mad & qashar, gunnah & bila gunnah, waqaf wal ibtida'), and art. Apart from that, students still make mistakes with letters and with punctuation marks (al-Qur'an letters lined up in a row, dead/sukun marks, tasydid marks; don't understand mad and qashar, let alone waqaf wal ibtida').